A single-cell atlas of mouse olfactory bulb chromatin accessibility. (20th February 2021) - Chen, Yin; Ding, Xiangning; Wang, Shiyou; Ding, Peiwen; Xu, Zaoxu; Li, Jiankang; Wang, Mingyue; Xiang, Rong; Wang, Xiaoling; Wang, Haoyu; Feng, Qikai; Qiu, Jiaying; et al.
Abstract: Olfaction, the sense of smell, is a fundamental trait crucial to many species. The olfactory bulb (OB) plays pivotal roles in processing and transmitting odor information from the environment to the brain. The cellular heterogeneity of the mouse OB has been studied using single-cell RNA sequencing. However, the epigenetic landscape of the mOB remains mostly unexplored. Herein, we apply single-cell assay for transposase-accessible chromatin sequencing to profile the genome-wide chromatin accessibility of 9, 549 single cells from the mOB. Based on single-cell epigenetic signatures, mOB cells are classified into 21 clusters corresponding to 11 cell types. We identify distinct sets of putative regulatory elements specific to each cell cluster from which putative target genes and enriched potential functions are inferred. In addition, the transcription factor motifs enriched in each cell cluster are determined to indicate the developmental fate of each cell lineage. Our study provides a valuable epigenetic data set for the mOB at single-cell resolution, and the results can enhance our understanding of regulatory circuits and the therapeutic capacity of the OB at the single-cell level.